The implementation of population education in senior high school - Claver Nzobonimpa; Zamroni Zamroni (Universitas Negeri Yogyakarta, 2018)
This research aimed to evaluate the implementation of Population Education in senior high school in terms of (1) learning process, (2) learning materials, (3) evaluation process, (4) course outcome, (5) teachers' role, (6) perception of Population Education, and (7) factors supporting and inhabitting Population Education. The research subjects were one teachers' supervisor, three teachers, and 65 students. The data were collected through questionnaires, interviews, and documentation and analyzed quantitatively using descriptive statistics. The qualitative data collected through interviews were used for deeper explanation. The research findings were: (1) the teaching process was not quite appropriate, (2) materials for Population Education were available and efficient, (3) the evaluation process was not appropriate, (4) the students were satisfied with the teachers' role, (5) the students' perception of Population Education was very positive, and (6) the constraints in Population Education included (a) limitation in time, (b) too many extracurricular activities, (c) rapid change of data, and (d) the validity of materials.